Learning from teaching: Exploring the relationship between reform curriculum and equity - Boaler, Jo (Journal for Research in Mathematics Education, 2002)
Some researchers have expressed doubts about the potential of reform-oriented curricula to promote equity. This article considers this important issue and argues that investigations into equitable teaching must pay attention to the particular practices of teaching and learning that are enacted in classrooms. Data are presented from two studies in which middle school and high school teachers using reform-oriented mathematics curricula achieved a reduction in linguistic, ethnic, and class inequalities in their schools. The teaching and learning practices that these teachers employed were central to the attainment of equality, suggesting that it is critical that relational analyses of equity go beyond the curriculum to include the teacher and their teaching.
Keywords: apprentissage par projet; efficacité; enseignement secondaire; genre; inégalité sociale; pratique pédagogique; réforme de l'enseignement